Dimensionamento preliminar de um sistema propulsivo para uma embarcação movida à energia solar - PIRES, Jerison Dias (2022)
The following work consists in design propulsion system that will be used to move a boat powered by solar energy that will be used in the event titled Solar Challenge Brazil. The propulsion system seen here is an assembly involving an electric motor, a propeller, a tail, and a reducer. The first step in the design of this system involved the estimation of the boat advance resistance, this resistance was estimated with the MaxSurf software aid, later to that fact, a propeller of the propeller type was defined that was able to move the boat in the speed of 5.5 knots without cavitation above 2.5%. Thus a tail was selected appropriate to the maximum draft size. Finally, because the engine did not meet the rotation and torque needed by the propeller, a reduction was necessary. This reduction is to approximate the engine rotation and torque to the propeller rotation and torque, its design was carried out in a way to withstand the generated efforts without interfering in their gear.